Penghijauan Kembali Kampungku: Upaya Kolaboratif Meningkatkan Kualitas Lingkungan di Desa Pagedangan, Tukdana, Indramayu - Sumarta, Sumarta (Kusuma: Jurnal Pengabdian kepada Masyarakat, 2024)
This community-driven initiative, "Re-greening My Village: A Collaborative Effort to Enhance Environmental Quality in Pagedangan Village, Tukdana, Indramayu," addresses the pressing need for environmental improvement through collaborative reforestation and greening efforts. Recognizing the environmental challenges faced by Pagedangan, this project engaged residents, local authorities, and relevant stakeholders in a participatory approach to enhance the village's environmental quality. Activities included the selection of appropriate native plant species, community planting drives, educational workshops on environmental stewardship, and the establishment of monitoring mechanisms for long-term sustainability. The project aimed to increase green cover, improve air and soil quality, enhance biodiversity, and foster a sense of environmental responsibility among villagers. The success of this collaborative endeavor highlights the potential of community-led initiatives in addressing environmental degradation and promoting a healthier, more sustainable living environment in Pagedangan Village.